COST AND RETURNS ANALYSIS OF INTERCROPPED TEA FARMS IN TARABA STATE, NIGERIA - OLUYOLE , K. A; OLADOKUN , Y.O.M; YAHAYA , A.T; DADA , A.O (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
In Taraba state, Nigeria, tea farming is predominant and it provides a source of employment for the local people around the Mambilla plateau and consequently boosts the national economy. This study assessed the costs and returns accruable in tea intercropped farms in Taraba State, Nigeria. A structured questionnaire was used to obtain information from 204 tea farmers in the study area. Descriptive Statistics and Ordinary least square regression was used in the data analysis. About 54% of the tea farmers are in Kakara town while the remaining 46% are in Sabongari, Mayo kusuku and Nyiwa towns. About 97% of the tea farmers are male, 71% are between 31 and 60 years and 84% are married. Four of the ten tea farmers who practice intercropping have no formal education. About 52% belong to cooperative societies. The average total cost per hectare per year and the average gross revenue per hectare per year are ₦8,686.16 and ₦6,026,342.45, respectively. The coefficients of labour cost, weeding, labour cost on other crops, cost of material (file), cost of material (chemical), and cost of material (bag) are all positive and significant. The proportion of the net income to the total cost is 68.6%. Hence, 68.6% of the total cost expended on tea intercrop production was generated as profit. Government at all levels; stakeholders in the tea industry should provide the needed resources for tea farmers to increase their production thus improving their wellbeing.